The Impact of Gravity‐Driven Sedimentation on Reshaping the Huanghe (Yellow River) Delta Front. Issue 11 (6th November 2022) - Liu, Shihao; Goff, John A.; Gao, Shu; Feng, Aiping; Wang, Ya Ping; Jia, Jianjun; Hu, Weifen; Feng, Wei; Yu, Yonggui
Abstract: Many of the world's mega‐river deltas are currently degrading due to a shortage of sediment supply feeding their construction. Here, using bathymetric and seismic data, the geomorphological/sedimentary evolution on and near a recently abandoned (1976 CE) Huanghe delta lobe is investigated. The delta front (DF) exhibits a lobe switching‐controlled pattern of progradation followed by mass wasting on the upper front, and redeposition at the seaward toe of the front; the latter process appears to be associated with sediment failure and contributes to delta degradation. During degradation, mass wasting‐driven deepening of the upper DF was initially up to ∼0.86 m/yr from 1978 to 1985 CE, slowed to ∼0.12 m/yr from 1985 to 2000 CE, and has been negligible since. In either prograding or degrading, gravity‐driven sedimentation results in a downlapping seismic unit superimposed on the bottomset of an earlier converging clinoform, with numerous buried/exposed submarine channels at its seaward terminus. These units exhibit a shore‐parallel elongated and continuous geometry, suggesting lateral spreading, which we attribute to alongshore hydrodynamic (especially tidal) remolding. Our findings underscore the significance of sediment gravity flows in the evolution of a degrading delta front, particularly as a principal mechanism of downslope mass transport that gentled (halving the gradient) and reshaped the DF over time. Gravity‐driven accumulations sourced from upper DF collapse can account for ∼1/3 of the previous DF and laterally extend over an unexpectedly large area (∼60‐km long) through hydrodynamic redistribution. Both processes should be considered for modeling other subaqueous deltas. Plain Language Summary: At underwater river deltas, gravity can cause sediment to flow downhill, which alters geological, chemical and biological processes and poses hazards to human infrastructures. Due to changes in the river on land, delta lobes can switch from one part of the coast to another, which alters the conditions that cause gravity flows. Our understanding of how the gravity flows respond to channel switching is very limited. This paper reports on seven repeated bathymetric surveys and a seismic survey collected at a recently abandoned Huanghe (Yellow River) delta lobe over four decades. We found that the gravity flows take place both when the delta lobe is active and after abandonment. Gravity flows make the underwater delta slope gentler by taking away sediment from the upper slope and moving it to the lower slope. This happened rapidly within the first decade after abandonment and slowed down thereafter. The redeposited sediments were spread out parallel to the shoreline by ocean currents. Our study highlights the significance of gravity flows in reshaping the underwater delta slope after abandonment, which may provide implications for enabling better societal response to the global deltaic degradation caused by reductions in river sediments transported to oceans. Key Points: Sediment gravity flows reshape and gentle the abandoned delta front (DF) slope over time Gravity flows dominated delta degradation via mass wasting on the upper DF and accumulating on the lower front Gravity‐driven sedimentation laterally spread over decadal span likely due to hydrodynamic redistribution